National food systems: Inclusive transformation for healthier diets - McDermott, John; de Brauw, Alan (International Food Policy Research Institute, 2020)
Policymakers need to know what policies, investments, and actions they can take to ensure food systems transform in a healthy, sustainable, and equitable way. KEY FINDINGS - The rapid transformation of national food systems offers new opportunities for inclusion of poor and marginalized people, potentially improving dietary diversity, food safety, and quality. - As food systems transform across the spectrum from traditional to modern, government policy goals need to shift from a focus on food security to healthy, bal-anced diets. - National food system frameworks are useful tools for looking at the drivers and components of these systems, identifying data gaps, and finding promising entry points for actions to increase inclusion and improve nutri-tion outcomes. - Approaches to food system transformation must be country specific, as each country’s food system is unique and countries face different opportunities and trade-offs for inclusiveness at different stages of transformation.